Porting MeeGo to LEON - Bertona, Ivan (My University, 2011)
Portable multimedia devices are the agship of a steadily growing market, from which the LEON/GRLIB hardware platform was excluded due to the lack of suitable software support. This thesis work addressed such problem by initiating a port effort of MeeGo, a Linux-based mobility-oriented operating system, to the SPARC-compatible LEON processor and to the hardware components provided by the GRLIB IP core library. The build infrastructure of MeeGo was modified and set up accordingly, and a partially working but usable MeeGo port was produced. The LEON/GRLIB platform was evaluated from a multimedia application stand- point. Lacking areas such as OpenGL hardware acceleration were pinpointed and the necessary improvements outlined.
Keywords: Information Technology; Informationsteknik